Research trends in the field of Islamic Banking and Finance: Bibliometric analysis from 2000 to 2024 - Muhammad Raihan Abu Bakar; Anwar Allah Pitchay; Mohamad Isa Abd Jalil (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2025)
This study presents a comprehensive bibliometric analysis of Islamic Banking and Finance (IBF) from 2000 to 2024, aiming to address research gaps, examine publication trends, and propose future research directions. Using a systematic search across five academic databases—Web of Science, ResearchGate, Google Scholar, Connected Papers, and Emerald Insight—150 peer-reviewed studies were selected based on relevance and quality. Analytical tools such as Biblioshiny (RStudio), VOS viewer, and Microsoft Excel were employed to map out the intellectual landscape of IBF. The findings highlight a strong research focus on Islamic banking operations, rate comparisons with conventional banks, and governance structures, while also uncovering patterns in geographical research output, citation networks, and collaboration trends. Importantly, the study identifies critical gaps in the literature, including a scarcity of empirical work on sustainable development, inadequate frameworks for institutional accountability, and limited exploration of digitalization and fintech in IBF. These insights form the basis for a proposed research agenda to steer future scholarship towards more impactful and globally relevant contributions.